Family firms: In all shapes and sizes - Emma Gunnarsson; Anders Kärnä; Martin Olsson; Lars Persson (Research Institute of Industrial Economics (IFN), 2023)
We study the heterogeneity of family firms using registry data on all private firms in Sweden. We restrict our sample to firms with at least one employee, and we define a family firm as a firm where two or more individuals among the owners or the board of directors are related. We focus on the heterogeneity in ownership, employee, and firm characteristics among family firms. We provide several new facts about family firms. The number of family members in family firms varies, consisting predominantly of two relatives, but a substantial share feature four or more. The share of multigenerational family firms has increased over time as has the share of women as owners and CEOs. Family firms employ more old and young workers, have a more compressed wage structure with a lower mean, and have a less compressed tenure distribution with a higher mean. The family firm age distribution is less compressed with a higher mean, and their location distribution is more equally distributed among metropolitan, urban, and rural areas.
Keywords: D22; D24; L25; L60; M11; M50; 330; Family Firms; Firm Organization; Employee Characteristics